Monkeypox Correlations: Genital Symptoms, Immunocompromised Status and MSM - El Boghdady Michael; Youssef Mark; Ewalds-Kvist Béatrice Marianne; Nada Hany (India, 2025)
Objectives: The outbreak of the virus infection Monkeypox (Mpox) in England was on transmission level 2. Mpox and HIV infections may occur simultaneously among the MSM population, exacerbating the symptoms along with treating problems. We aimed to study if Mpox painful genital symptoms correlated with immunocompromised status, sexuality, admissions and length of hospital stay.
Methods: A retrospective data analysis was conducted. The admissions were divided into four groups named: perianal, penile, rectal and other symptoms. Correlations between patients’ pain groups, sexuality or immunocompromised status as well as length of hospital stay were studied. Significances were computed by Spearman’s rho correlation and Kruskal-Wallis H analyses of variance.
Results: Sixty-nine patients were included, 65 males with mean age=38,5 (SD 8.29; Md=39) and females’ mean age=35.5 (SD 9.04; Md= 39.5) years (n.s.). The two gender’s Mpox pain areas differed from each other (p= .014). A total of 38% of the male patients presented painful perianal or rectal lesions and 22 males displayed general symptoms and 17 acknowledged MSM. A total of 40% of the males were sexually active with multiple partners; an inverse correlation between males with MSM and males with HIV (rho [25] = -.385*, p= .029, 1-tailed) was revealed. Altogether 23% of males presented HIV and 8% suffered from additional STI. Those with rectal pain had the longest hospital stay with a mean of 6.0 (SD 7.63) days (p= .017) compared to other groups.
Conclusion: Correlations between patients diagnosed with Mpox and genital symptoms were revealed as opposed to inverse correlations between immunocompromised status/HIV and MSM.